DIGITALIZATION OF ROMANIAN PRE-UNIVERSITY EDUCATION IN CORONAVIRUS PANDEMIC CONDITIONS (Annals of the University of Bucharest. Geography Series, 2024)
The article analyzes the decisions regarding the implementation of the online education system in Romania as a result of the health crisis caused by Covid-19. The analysis was carried out in the period between the establishment of the state of emergency (March 2020) and the repeal of the state of alert (March 2022), during the first pandemic waves in Romania. General bibliographic resources, elements of the legislative framework andinformation from mass media were used. The conclusions highlight a lack of coherence in the management of educational activities during this period, embodied in the frequent change of criteria according to which the transition was made from educational activities with physical presence to those in the online system. This favored the intensification of the virus circulation during certain periods of the pandemic, contributed to widening social gaps between students and limited the usefulness of some investments incomputer technology for students' access to online education.
Keywords: digitization; online education; pandemic; management of educational activities; Romania